A RFID switch beam scanning antenna array for application in complex environment. Issue 1 (2nd January 2019) - Zhu, Hua; Li, Xiuping; Li, Quanping; Feng, Weiwei
ABSTRACT: This paper presents a radio-frequency identification (RFID) switch beam scanning antenna array for application in metal environment. Three 1 × 2 planar inverted-F antenna arrays are designed with a driven element and two parasitic elements. Three elements are controlled by a switch feeding network consisting switch and control module. The size is 300 × 600 × 11.6 mm 3 . The measured −10 dB impedance bandwidth is 50 MHz (895–945 MHz). The proposed antenna array is capable of steering the radiation pattern to −20°, 0°, and +25° in xoz -plane. The scanning beam direction gain reached 9.4 dBi. The measured and simulated results agree well. The reading rate achieves 100% in a metal environment.